Giant lactating adenoma - Isac Ribeiro Moulaz; Fernanda Sales Soares de Oliveira; Eveline Cristina da Silva Cristina da Silva; Janine Martins Machado; Maria Carmen Lopes Ferreira Silva Santos (University of São Paulo, 2021)
Lactating adenoma is a rare benign breast lesion that most often presents as a small (up to 3 cm), solid, well-circumscribed, solitary, painless, mobile, lobulated mass. The highest incidence occurs in primiparous women (20 to 40 years old) during the third trimester of pregnancy. However, in the rare case presented herein, in addition to its giant size (more than 10 centimeters on palpation), this lactating adenoma is distinctive due to the presence of multiple nodules, poorly defined ultrasonographic margins, worrisome radiologic features, growth since early pregnancy, presence of infarction and association with chronic mastitis. From the clinical-radiologic perspective, the differential diagnoses included abscess associated with puerperal mastitis, phyllodes tumor, and galactocele. Biopsy was performed, and pathologic examination revealed the classic characteristics of lactating adenoma with multiple infarcted areas, leading to an unexpected confirmed case of giant lactating adenoma.